A oralidade como técnica de redução das práticas autoritárias no processo penal - Maya, André Machado (2015)
The present investigation, to examine the evidential initiative value of the judge under the criminal procedural law, is part of the research line of Contemporary Criminal Legal Systems, which integrates the area of Criminal System and Violence of the Graduate Program from Pontifícia Universidade Católica do Rio Grande do Sul (PUCRS). This study starts from the relationship between the State, the law and the criminal procedure, in an approach to the theory of legal field from PIERRE BOURDIEU, to locate the criminal procedural law as a small field of state political fiefdom, which operates in accordance with internal specific rules and also to external political influences, resulting that the process model is directly related to the type of State, its way of justice administration and its form of government to indicate their way of relating to citizens. Thereby, while under the democratic states the jurisdiction is conceived as a focused counter-power to guarantee individual freedoms, resulting inadequate any probative initiative of the judge in criminal matters, within the limits of authoritarian interventionist States, in which the jurisdiction is the embodiment of the sovereign power, it is natural having conclusive initiative, essential to the revelation of the truth that legitimizes the punitive power. In this context, the probative initiative of the judge in the criminal process is identified in this study as an authoritarian practice which, reformulated, remains strong even in the current democratic setting. Assuming this premise, this research supports that, to the democratization of criminal proceedings, the strengthening of effectiveness of contradictory is essential, for what seems fundamental the oral procedure.By imposing the concentrated practice of procedural acts, orality provides a connection between evidences, parties and judge, strengthening the contradictory. Moreover, by materializing in the process the theory of separation of powers, contributes to the formatting of a subjectively balanced process, polycentric and without leading role. In this context, the thesis holds orality as an approximation technique between normativity and effectiveness of the democratic principle applied in the process and, consequently, the reduction of authoritarianism in criminal proceedings.